2022
DOI: 10.3389/fimmu.2022.930352
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a six-gene prognostic signature for bladder cancer associated macrophage

Abstract: As major components of the tumor microenvironment (TME), tumor-associated macrophages (TAMs) play an exceedingly complicated role in tumor progression and tumorigenesis. However, few studies have reported the specific TAM gene signature in bladder cancer. Herein, this study focused on developing a TAM-related prognostic model in bladder cancer patients based on The Cancer Genome Atlas (TCGA) data. Weighted Gene Co-Expression Network Analysis (WGCNA) was used to identify key genes related to TAM (M2 macrophage)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
(49 reference statements)
0
14
0
1
Order By: Relevance
“…Nine studies validated their hypothesis by in-house experiments [ 42 50 ]. Five studies validated their hypothesis by analyzing other databases [ 51 55 ].…”
Section: Resultsmentioning
confidence: 87%
“…Nine studies validated their hypothesis by in-house experiments [ 42 50 ]. Five studies validated their hypothesis by analyzing other databases [ 51 55 ].…”
Section: Resultsmentioning
confidence: 87%
“…Next, the 3-gene prognostic model was established by univariate Cox regression analysis and LASSO algorithm, involving: MAP1B, PCOLCE2, and ELN, with the ROC curve results demonstrating that it had promising predictive efficacy for prognosis and was an independent prognostic factor for OS in BLCA. Contrary to other models [ 33 ], our signatures were the results of integrating multiple datasets and algorithms, validated by internal and external validation sets inconsistent with the training set, and showed AUC values between 0.590–0.813, suggesting higher reliability and relevance, of which we also analyzed the relationship between the model and clinicopathological characteristics, and the results revealed that risk scores were significantly associated with patients' lymph node metastasis and tumor stage, indicating that the model is not limited to having predictive value for OS. Besides, we also observed 3 signature genes related to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, using the GSE13507 dataset as an external test set, we found that the risk score calculated by the MMRS model was an adverse prognostic factor for bladder cancer patients ( Figure 2 D). We also compared two published M2 macrophages-based prognostic models in bladder cancer, 17 , 18 and time-dependent area under curve (AUC) analysis showed that MMRS had higher predictive power ( Figure 2 E). Decision curve analysis (DCA) showed that MMRS had the highest net benefit compared with other models when predicting overall survival (OS) at 1, 3, and 5 years ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 99%